2015
DOI: 10.1002/term.2110
|View full text |Cite
|
Sign up to set email alerts
|

Octacalcium phosphate collagen composite facilitates bone regeneration of large mandibular bone defect in humans

Abstract: Recently it was reported that the implantation of octacalcium phosphate (OCP) and collagen composite (OCP-collagen) was effective at promoting bone healing in small bone defects after cystectomy in humans. In addition, OCP-collagen promoted bone regeneration in a critical-sized bone defect of a rodent or canine model. In this study, OCP-collagen was implanted into a human mandibular bone defect with a longer axis of approximately 40 mm, which was diagnosed as a residual cyst with apical periodontitis. The amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…This study demonstrated the safety and efficacy of OCP/Col, as a primary endpoint, on bone regeneration in maxillary sinus floor augmentation, as did previous clinical studies on application in human extraction tooth cavities and oral cystic cavities. 6,16,17 No clinical complications such as significant infection, severe inflammation or pain were seen beside the usual course associated with surgery, sensory disorders, and abnormal bone resorption caused by OCP/Col. Likewise, no systemic complications were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated the safety and efficacy of OCP/Col, as a primary endpoint, on bone regeneration in maxillary sinus floor augmentation, as did previous clinical studies on application in human extraction tooth cavities and oral cystic cavities. 6,16,17 No clinical complications such as significant infection, severe inflammation or pain were seen beside the usual course associated with surgery, sensory disorders, and abnormal bone resorption caused by OCP/Col. Likewise, no systemic complications were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kanda et al have shown that OCP/Col does not interfere with eruption of the following permanent tooth when OCP/Col is implanted after deciduous tooth extraction in a young canine model . Furthermore, OCP/Col has also proven to offer not only safety, but also efficacy in bone regeneration on clinical studies of application to human tooth extraction sockets and cystic cavities . Therefore, the demand of alveolar ridge augmentation (including maxillary sinus floor augmentation) is also increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OCP/Col is expected to enhance physiological bone remodeling, is easy to handle, and has excellent cost performance. After the confirmation of bone regeneration by OCP/Col in various canine bone defect models,10, 11, 12, 13 a doctor‐initiated clinical study was performed on tooth extraction sockets and cyst holes 14, 15. A sponsor‐initiated clinical trial was recently conducted and the commercialization of OCP/Col appears to be forthcoming.…”
Section: Introductionmentioning
confidence: 99%
“…After the confirmation of bone regeneration by OCP/Col in various canine bone defect models, [10][11][12][13] a doctor-initiated clinical study was performed on tooth extraction sockets and cyst holes. 14,15 A sponsorinitiated clinical trial was recently conducted and the commercialization of OCP/Col appears to be forthcoming. However, bone regeneration by OCP/Col alone has limited availability, and, thus, the development of more reliable bone regeneration is anticipated.…”
Section: Introductionmentioning
confidence: 99%